2018
DOI: 10.1002/anie.201803228
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Reductive Cross‐Coupling of Aryl Halides with Monofluoroalkyl Halides for Late‐Stage Monofluoroalkylation

Abstract: A combinatorial nickel-catalyzed monofluoroalkylation of aryl halides with unactivated fluoroalkyl halides by reductive cross-coupling has been developed. This method demonstrated high efficiency, mild conditions, and excellent functional-group tolerance, thus enabling the late-stage monofluoroalkylation of diverse drugs. The key to success was the combination of diverse readily available bidentate and monodentate pyridine-type nitrogen ligands with nickel, which in situ generated a variety of readily tunable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 80 publications
1
34
0
2
Order By: Relevance
“…Furthermore, we examined the influence of additives and solvent. As previously reported, pyridine and its derivatives could facilitate Ni‐catalyzed reductive coupling reactions. Therefore, various pyridine derivatives were examined and the yield of 3 a was increased to 25% in the presence of 4‐( N , N ‐dimethylamino)pyridine (DMAP) (Table , entry 8).…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, we examined the influence of additives and solvent. As previously reported, pyridine and its derivatives could facilitate Ni‐catalyzed reductive coupling reactions. Therefore, various pyridine derivatives were examined and the yield of 3 a was increased to 25% in the presence of 4‐( N , N ‐dimethylamino)pyridine (DMAP) (Table , entry 8).…”
Section: Methodssupporting
confidence: 54%
“…Therefore, various pyridine derivatives were examined and the yield of 3 a was increased to 25% in the presence of 4‐( N , N ‐dimethylamino)pyridine (DMAP) (Table , entry 8). On the contrary, 4‐cyanopyridine (4‐CN−Py), used in nickel‐catalyzed monofluoroalkylation of aryl halides, resulted in little product 3 a (Table , entry 11). For solvent screening, it was found that DMSO is better than DMF, DMA and NMP (Table , entries 8, 13–15).…”
Section: Methodsmentioning
confidence: 99%
“…[14] We found that the b-fluoroalkyl electrophile (FCH 2 CH 2 I) kept untouched under the treatment of manganese powderi nN MP at 80 8C( Scheme 5d)o ru nder the standard condition A in the absence of aryl chloride (Scheme5e). [14] We found that the b-fluoroalkyl electrophile (FCH 2 CH 2 I) kept untouched under the treatment of manganese powderi nN MP at 80 8C( Scheme 5d)o ru nder the standard condition A in the absence of aryl chloride (Scheme5e).…”
Section: Resultsmentioning
confidence: 94%
“…Attempts to improve the reaction outcomev ia employing combinatorial ligand system [14] were unsuccessful by screening within as eries of pyridinyl monodentate ligandsw hich are decorated by either electron-donating or electron-withdrawingg roups ( Table 1, entries [8][9][10][11][12][13]. Further interrogation on the structuralm otifs of bidentate nitrogen ligands indicated that the electron-rich 4,4'-dimethoxy-2,2'-bipyridine (dmobpy) with steric-unhinderedc oordination site was optimal and improved the coupling yield to 77 % ( Table 1, entries [14][15][16][17][18]. Finally,c ontrol experiment indicated that both the nickel salts and supporting ligands werei ndispensablefor the success of this coupling (Table 1, entry 19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation